(untitled) (Global Journal of Human-Social Science, 2025)
The purpose of this article is to highlight the role played by remittances from international migrants in access to healthcare for Cameroonian households. It uses the instrumental variables approach to address the endogeneity problem associated with the migrant remittances variable. Using data from the fourth Cameroonian household survey (ECAM 4), the results obtained with the instrumental variables method (IV-2SLS) converge with those obtained using the generalised method of moments (GMM) and highlight the dual role played by remittances in access to healthcare. On the one hand, they show that households receiving these transfers change their choice of healthcare facilities in favour of private healthcare units. On the other hand, these results more generally show that remittances enable households to meet their basic needs and thus change their position according to Engel’s law (1857). Thus, public authorities should improve the incentive framework for these transfers, not only to combat monetary poverty but also to improve life expectancy and reduce mortality rates.